The "Homeric Hymn to Aphrodite" and Related Texts Text, Translation and Commentary. (de Gruyter, 2012)
The Homeric Hymn to Aphrodite (600s BCE?) tells the story of a brief encounter between the goddess of love and the cowherd Anchises, which led to the birth of the Trojan hero Aeneas. Less than 300 lines long, it is among the shortest of the so-called 'major Homeric Hymns', but is nonetheless richly and beautifully conceived and narrated. This book offers a complete text of the poem and of nine related 'minor Hymns', based on a fresh examination of the manuscripts. Also offered are a translation; a substantial introduction, which treats inter alia the problem of dating early Greek epic poetry; and a narratologically-oriented commentary.
Anchises, Aeneas, and the Aeneidae -- Date of composition -- Poetic affiliations of the Homeric hymn to Aphrodite -- Aphrodite and sexuality -- The metrics of the Homeric hymn to Aphrodite -- Textual transmission -- Critical text and translation: Hymn 5: to Aphrodite -- Hymn 6: to Aphrodite -- Hymn 9: to Artemis -- Hymn 10: to Aphrodite -- Hymn 11: to Athena -- Hymn 12: to Hera -- Hymn 24: to Hestia -- Hymn 27: to Artemis -- Hymn 28: to Athena -- Hymn 29: to Hestia -- Commentary: Hymn 5: to Aphrodite -- Hymn 6: to Aphrodite -- Hymn 9: to Artemis -- Hymn 10: to Aphrodite -- Hymn 11: to Athena -- Hymn 12: to Hera -- Hymn 24: to Hestia -- Hymn 27: to Artemis -- Hymn 28: to Athena -- Hymn 29: to Hestia.
Includes bibliographical references (pages 321-325) and index.
In English with scattered Greek.
Master record variable field(s) change: 630
Keywords: Homeric hymns; Hymn to Aphrodite (Homeric hymn 5); Hymn to Aphrodite (Homeric hymn 5) -- Criticism, interpretation, etc; Homerus, -- approximately 8. Jh v. Chr; Homeric hymns; Hymn to Aphrodite; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; Homerus, -- approximately 8. Jh v. Chr; LITERARY CRITICISM -- Ancient & Classical; Electronic books; Criticism, interpretation, etc